RANCANG BANGUN E-LEARNING 2.0 BERBASIS WEBSITE PADA BALAI PENGEMBANGAN TENAGA KERJA (BPTK) DJOGJA BHAKTI UTAMA - Marhayu Marhayu; Viktor Handrianus Pranatawijaya; Tri Amri Wijaya (Universitas Palangka Raya, 2014)
Along with the development of information technology is growing rapidly, the need for a conceptand mechanism of IT-based teaching and learning becomes inevitable. As an agency ManpowerDevelopment Center